Designed, Synthesis, In Vitro and Computational Analyses of Anticancer Nicotinamide Derivatives (Indian Journal of Chemistry (IJC), 2024)
The search for ideal treatment continues for many health problems such as cancer and infection. In this context, new synthesis compounds have been promising and the nicotinamide derivative compounds, which is an important heterocyclic derivative, has attracted the attention of many researchers. Nowdays, anticancer, antifungal, antimicrobial, antibacterial and antibiofilm effects of some Nicotinamide derivatives have been demonstrated. In this study, nine new nicotinamide derivative compounds were designed and synthesized. The characterization of these synthesized compounds was done by in-silicone methods. The anticancer effects of the compounds were investigated in four different cancer types and compared with their effects on healthy fibroblast cells. N4 was found to have a cytotoxic effect on MCF-7 human breast cancer, and the IC50 value was calculated as 12.1 μM. In addition, Antibacterial, Antifungal and Antibiofilm activities were investigated by in vitro methods and they were shown to be effective. As a result, it was observed that N4, one of the newly synthesized nicotinamide derivative compounds, had a serious cytotoxic effect in MCF-7 human breast cancer cells compared to healthy fibroblast cells. They have also been shown to have remarkable Antibacterial, Antifungal and Antibiofilm activities, especially N2 and N3. Additionally, anticancer properties of studied compounds are investigated using in silico techniques. Pharmacophore map and ADME analyses of studied compound are performed in detail.